2023
DOI: 10.3389/fmicb.2023.1190650
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits and risks of solar photovoltaic power plants on arid and semi-arid ecosystems: an assessment of soil microbial and plant communities

Abstract: Exponential increase in photovoltaic installations arouses concerns regarding the impacts of large-scale solar power plants on dryland ecosystems. While the effects of photovoltaic panels on soil moisture content and plant biomass in arid ecosystems have been recognized, little is known about their influence on soil microbial communities. Here, we employed a combination of quantitative PCR, high-throughput sequencing, and soil property analysis to investigate the responses of soil microbial communities to sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The annual precipitation in the NMC area is the highest among the three sample points, indicating that precipitation and endophyte diversity are closely related. Previous studies have shown that differences in precipitation will lead to differences in soil microorganisms, and annual precipitation is positively correlated with soil microbial diversity 42 , 43 . In addition, among the three sample points, the NMC sample point has the highest pH and salinity value (pH 8.5, salinity 3 ms/cm), followed by XGYZ (pH 8.2, salinity 0.05 ms/cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual precipitation in the NMC area is the highest among the three sample points, indicating that precipitation and endophyte diversity are closely related. Previous studies have shown that differences in precipitation will lead to differences in soil microorganisms, and annual precipitation is positively correlated with soil microbial diversity 42 , 43 . In addition, among the three sample points, the NMC sample point has the highest pH and salinity value (pH 8.5, salinity 3 ms/cm), followed by XGYZ (pH 8.2, salinity 0.05 ms/cm).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that not only different plants have different endophytic community structures, but also there are generally differences in the endophytic community structures of the same species under different geographical conditions, such as the medicinal plants Codonopsis pilosula , Astragalus membranaceus , and Forsythia suspensa on the Qinghai-Tibet Plateau. Such geographical differences also exist in the diversity of endophytes 42 .…”
Section: Discussionmentioning
confidence: 99%